2001
DOI: 10.1103/physreve.63.055103
|View full text |Cite
|
Sign up to set email alerts
|

Boundary lubrication:  Dynamics of squeeze-out

Abstract: The dynamics of the expulsion of the last liquid monolayer of molecules confined between two surfaces (measured recently for the first time) has been analyzed by solving the two-dimensional Navier-Stokes equation combined with kinetic Monte Carlo simulations. Instabilities in the boundary line of the expelled film were observed. We show that the instabilities produce a rough boundary for all length scales above a critical value and a smooth boundary for shorter lengths. The squeezing out of all but a few trapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 19 publications
3
38
0
Order By: Relevance
“…In our experiments, u c : 5 mm. Recent Monte Carlo simulations showed that the length scale of the boundary line can be reproduced provided that the line energy is incorporated into the model appropriately [6]. The simulations also showed that the increasing roughness eventually leads to the detachment of liquid pockets from the moving boundary line, which become trapped inside the contact area.…”
Section: Layering Transitionmentioning
confidence: 83%
See 2 more Smart Citations
“…In our experiments, u c : 5 mm. Recent Monte Carlo simulations showed that the length scale of the boundary line can be reproduced provided that the line energy is incorporated into the model appropriately [6]. The simulations also showed that the increasing roughness eventually leads to the detachment of liquid pockets from the moving boundary line, which become trapped inside the contact area.…”
Section: Layering Transitionmentioning
confidence: 83%
“…The roughening of the boundary line can be explained in a similar fashion. Beyond a critical length u c , the boundary line is unstable with respect to deformations [14,6]. Any local perturbation of the boundary line produces segments that are closer to the edge of the contact area than others.…”
Section: Layering Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elimination of each layer starts with the nucleation of a 2D void, which progressively grows by ejecting atoms into the low pressure regions. 7,[9][10][11]12 We have shown earlier that the void formation is a thermally activated process, which, for 2D liquid-like layers, can be described by concepts borrowed from classical nucleation theory. 9 In many practical situations the nucleation of the layering transition may occur at some ''weak'' point between the surfaces where imperfections, e.g., foreign adsorbates ͑like water or some organic contamination͒, may locally reduce the spreading pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects have been observed for organic liquid films between mica surfaces. 8,9 Under certain conditions thin and uniformly thick fluid films remain trapped at the rubber/substrate interface. [10][11][12] The latter occurs when electrical charge is introduced upon contact of the surfaces leading to their electrical repulsion.…”
Section: Introductionmentioning
confidence: 99%